Covid-19 Virus Sterilization Oven Based on Combination Between Ultraviolet and Infrared Emissions - Shehataa, Mohamed; Adel, Abdelrahman; Hafez, Alaa; El-Hady, Ahmed; Youssef, Mohamed; Mabrouk, Mohamed (International Journal of Infection Prevention, 2020)
The world is countering an unexpected wide spread of Covid-19 virus. Among the procedures used to prevent spreading the virus are classical and modern sterilization methods. In this paper, we combine the use of ultraviolet emissions, as a modern method, with the infrared emissions that generates high temperature, as a classical method, to design and implement a sterilization oven. Ultraviolet emissions have the ability to destroy the RNA of the virus while the infrared emissions destroy the virus membrane. Test was performed on indicators contains +ve gram rod bacteria which is stronger than the Covid-19 virus in high temperature and UV emission tolerant. Results showed that the UV emissions killed the microorganism in 15 minutes. However, combination between the UV and IR emissions in a sterilization oven succeeded to kill the under test microorganism in five minutes. The combination between the two sources of emission guarantees an effective sterilization process against bacteria, fungus, and viruses. Moreover, it speeds up the sterilization process time.
Keywords: Healthcare Associated Infections; Cross Infection; Personal Protective Equipment